Critical Conditions Leading to Empyema Thoracis Among Patients in Thoracic Surgery Ward, Lady Reading Hospital Peshawar - Tahir Aslam; Amer Bilal; Abdul Baseer; Abid Khan; Manzoor Ahmed; Arslan Ahmed Salam (Pakistan Journal of Medical Research, 2020)
Background: Emphysema Thoracis, an infectious condition is a historically recognized clinical problem with annual incidence of up to 80,000 cases worldwide. Despite the advent of effective antibiotics it has considerably high morbidity and mortality in the population especially in low resource settings.